Learning Using Visual Media to Increase Student Learning Motivation at UPTD SDN 1 Kertasemaya - Novia Ramdhani; Diah Hani; Imelda Nurul Fitri; Fathul Fikri (Konsultan Jurnal Ilmiah Indonesia, 2025)
This Community Service entitled Learning Using Visual Media to Increase Students' Learning Motivation at UPTD SDN 1 Kertasemaya, provides learning to students at SDN 1 Kertasemaya regarding the subjects of mathematics, Islamic religion and counseling using teaching aids such as PPT, height measuring instruments. body, miniature gong, and spin. The method we use in learning is the Problem Based Learning method and Classical Guidance. This method is used in the entire series of management of community service implementation, both at the planning, implementation and evaluation stages. By involving (participating) students in planning, we can identify various expectations, needs and real problems faced by schools, so that we can develop more precise and realistic action plans. The results of this community service activity are factors that can increase students' learning motivation, including a strong sense of curiosity, clear goals, a conducive learning environment, social support from people around them, as well as awards and recognition for the achievements achieved by students, p. must be strengthened to improve student learning outcomes.